DAYA TARIK SEKTORAL, KARAKTERISTIK INDIVIDU, SERTA KESESUAIAN PILIHAN PEKERJAAN DAN PRODUKTIVITAS PEKERJA - - Susilo (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
The purpose of this study is to analyze the effect of sectoral effort factor, individualcharacteristic and job choice compability to labor productivity in agriculture andmanufacture sector at East Java. Using Structural Equation Modeling–SEM withAMOS (Analysis of Moment Structural) Application Program to analyze the surveyresult. The result shows that sectoral effort factor and individual characteristic havesignificant effect to labor productivity in agriculture and manufacturing sectors, whilejob choice compability doesn’t have significant effect to labor productivity. It meansthat sectoral effort factor and individual characteristic effects to labor productivityin agriculture dan manufactur sector doesn’t pass through job choice compability(intervening variable), but, it directly passes to labor productivity. Beside, this studycould prove that labor productivity in agriculture sector higher than labor produc-tivity manufacturing sector.Keywords: Sector effort factor, individual characteristic, job choise compability,labor productivity